Types Of Akad, Maturity, Company Size And Nominal Sukuk Price In Indonesia Stock Exchange (Idx) In 2016 - Dudi Abdul Hadi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Sukuk is currently a capital instrument of interest on the Indonesia Stock Exchange (IDX) because sukuk can increase profitability. The nominal price of the sukuk is influenced by maturity. But this maturity in 2016 is significant only at the 70% confidence level. This means that there is a lack of observation. This research was conducted to explore other variables that could affect the nominal price of the sukuk. It turns out that the size of the company affects the nominal price of the sukuk as well as the type of contract, maturity and maturity based on the type of contract. It turns out that the nominal value of the sukuk is influenced by the type of contract, the maturity is based on the contract, the type of contract based on maturity and the size of the company at the 95% confidence level.